Immunomodulatory activity of manganese dioxide nanoparticles: Promising for novel vaccines and immunotherapeutics - Huang, Yuhe; Ruan, Yongdui; Ma, Yuhe; Chen, Dongsheng; Zhang, Tangxin; Fan, Shuhao; Lin, Wensen; Huang, Yifan; Lu, Hongmei; Xu, Jun-Fa; Pi, Jiang; Zheng, Biying (Frontiers in Immunology, 2023)
Manganese (Mn), a nutrient inorganic trace element, is necessary for a variety of physiological processes of animal body due to their important roles in oxidative regulation effects and other aspects of activities. Moreover, manganese ion (Mn2+) has widely reported to be crucial for the regulations of different immunological responses, thus showing promising application as potential adjuvants and immunotherapeutics. Taking the advantages of Mn-based biological and immunological activities, Manganese dioxide nanoparticles (MnO2 NPs) are a new type of inorganic nanomaterials with numerous advantages, including simple preparation, low cost, environmental friendliness, low toxicity, biodegradable metabolism and high bioavailability. MnO2 NPs, as a kind of drug carrier, have also shown the ability to catalyze H2O2 to produce O2 under acidic conditions, which can enhance the efficacy of radiotherapy, chemotherapy and other therapeutics for tumor treatment by remodeling the tumor microenvironment. More importantly, MnO2 NPs also play important roles in immune regulations both in innate and adaptive immunity. In this review, we summarize the biological activities of Manganese, followed by the introduction for the biological and medical functions and mechanisms of MnO2 NPs. What’s more, we emphatically discussed the immunological regulation effects and mechanisms of MnO2 NPs, as well as their potentials to serve as adjuvants and immunomodulators, which might benefit the development of novel vaccines and immunotherapies for more effective disease control.